ANALISIS BIBLIOMETRIK (2010-2023): PENGARUH MSG TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA DINI - Widjayatri, Rr. Deni; Hapsari, Aldifta Putri; Damayanti, Dwi; Pramitha Sari, Zelika; Faradilla, Dea (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The rampant use of MSG in over-consumed foods can damage cells in children's brains. MSG can cause decreased brain function and can affect cognitive development, and nutritional balance. The purpose of the data analysis was conducted to determine the impact of MSG use on children's cognitive development. The analysis method involves a Systematic Literature Review (SLR) using a bibliometric analysis approach of literature studies with the Publish or Perish application and Google Scholar as a data source with a duration of 2010-2023. After processing the article data by selecting a special topic on “the effect of MSG use on children's cognitive development”, 200 relevant articles were obtained for review from 200 articles from the initial search results. The results of the study were then compiled meta data VOSViewer application was used to create a visualization of research trends. The results showed that the classification of analysis on the effect of MSG use on children's cognitive development into 3 clusters. (red, blue, green). All data from these clusters show that the effect of MSG on children's cognitive development is still a problem that needs attention. Therefore, parents should be more careful in providing nutritional intake to their children.